2018
DOI: 10.1002/mp.13233
|View full text |Cite
|
Sign up to set email alerts
|

Principal component analysis modeling of Head‐and‐Neck anatomy using daily Cone Beam‐CT images

Abstract: Purpose To model Head‐and‐Neck anatomy from daily Cone Beam‐CT (CBCT) images over the course of fractionated radiotherapy using principal component analysis (PCA). Methods and materials Eighteen oropharyngeal Head‐and‐Neck cancer patients, treated with volumetric modulated arc therapy (VMAT), were included in this retrospective study. Normal organs, including the parotid and submandibular glands, mandible, pharyngeal constrictor muscles (PCMs), and spinal cord were contoured using daily CBCT image datasets. PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…21 Principal component analysis is a multivariate technique widely used in dataset dimensionality reduction to increase interpretability while preserving most of the initial information. [22][23][24] . For that, PCA finds a new set of uncorrelated variables (principal components, PCs) that result from linear combinations of the original ones and that successively maximize variance.…”
Section: C | Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…21 Principal component analysis is a multivariate technique widely used in dataset dimensionality reduction to increase interpretability while preserving most of the initial information. [22][23][24] . For that, PCA finds a new set of uncorrelated variables (principal components, PCs) that result from linear combinations of the original ones and that successively maximize variance.…”
Section: C | Statistical Analysismentioning
confidence: 99%
“…8,9 Bresciani et al, 8 using 384 HT plans of multiple treatment sites, found no strong correlations between some of these factors and the results of pretreatment QA verification. Binny et al 9 have used multiple statistical process control methods on a set of head and neck (28), pelvic (19) and brain (23) plans, to define lower and upper limits for planning parameters, like the modulation factor, gantry period, and couch speed, based on acceptable pretreatment QA results. The established ranges were specific to each treatment site and contributed to improve the treatment efficiency at their institution.…”
mentioning
confidence: 99%
“…Previous studies have investigated the generation of PCA models in H&N cancer patients and their evaluation. For example, Tsiamas et al [15] , assessed the number of components needed to model the spatial displacements for specific organs, using data from 18 patients to create both individual and population-based models. They focused on comparing the relative variance of the different PCA components between models.…”
Section: Discussionmentioning
confidence: 99%
“…using robust or probabilistic planning [5] . Principal component analysis (PCA) is widely used for creating such models, for instance in lung [6] , [7] , [8] , [9] , prostate [10] , [11] , [12] , [13] , [14] , cervix [5] and head and neck (H&N) [15] , [16] . The usefulness of such models depends on their ability to accurately simulate future changes in the patient.…”
Section: Introductionmentioning
confidence: 99%
“…Anatomical models that simulate the possible geometric variations from a population of patient data remove the requirement of multiple scanning and the dependence of CT images acquired during the treatment by taking the predicted images into aRO. Several mathematical models have been proposed to account for anatomical changes (Yu et al 2016, Tsiamas et al 2018. Yu et al used an anatomical model for deformable image registration (DIR) evaluation.…”
Section: Introductionmentioning
confidence: 99%